Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan Melalui Motivasi Sebagai Variabel Intervening Studi pada PT. Rahmat Jaya Perkasa Sidoarjo - Najmy Haqq (Universitas Negeri Surabaya, 2018)
PT. Rahmat Jaya Perkasa is a company focuses on ceramic tiles distribution in East Java region. To improve and maintain the quality of its services, the company focuses on their organization culture. This process is done so that the organization within the company can improve employee performance to maintain its competitive advantage. In order to improve the performance of employees is needed motivation to work so that the organization can maintain its competitive advantage. Thus, the purpose of this study was to analyze the influence of organizational culture, employee performance and motivation. And the role of mediation motivation to work on the influence of organizational culture on employee performance. Samples from this study are all permanent employees of PT. Rahmat Jaya Perkasa, which are 42 employees. Data analysis technique used is the analysis with alternative methods of Structural Equation Model Partial Least Square with the help of software Smart PLS 3.0. The results of the study explained that organizational culture significantly influence employee performance. Organizational culture positive and significant effect on work motivation. Work motivation significantly influence employee performance. Work motivation is not mediating effect of organizational culture on employee performance.